Accommodation Dysfunction and Treatment in COVID-19: A Case Study. - Yan Ling Liang (Optometry & Visual Performance, 2025)
Background: Globally, COVID-19 infected more than 36.5 million and claimed over 1 million lives by October 2020. Recent evidence showed that SARS-COV-2 exhibits neurotropic properties and causes neurological diseases. Moreover, neurological manifestations can occur independent of the respiratory system. This can also lead to eye movement alterations, including accommodation and vergence. Case Report: A 39-year-old male, AU, was referred to our clinic by a local Traditional Chinese medicine and rehabilitation clinic. He came in for a neurooptometric vision evaluation. He complained of general fatigue, visual fatigue, and headaches since he was diagnosed with COVID-19 infection two weeks prior. The evaluation revealed that AU had reduced visual acuity at distance, accommodative dysfunction, vergence dysfunction, and poor local stereopsis. The patient also experienced constricted kinetic fields. Treatment included home-based syntonic photobiomodulation, neuro-optometric rehabilitation therapy (NORT), and modified low-plus lenses in an anti-fatigue lens format for distance and near. After 14 weeks of photobiomodulation and 12 sessions of neuro-optometric rehabilitation therapy, the patient reported a reduction in the number and frequency of headaches, with normalized near point of convergence, improved near vergence ranges, and improved accommodative flexibility and ranges. After 23 weeks of photobiomodulation and 20 sessions of neuro-optometric rehabilitation therapy, he reported increased focus and reduced blur when reading, less visual fatigue, and a continued reduction in the frequency and duration of headaches. He also showed improved distance vergence ranges and regained more accommodative flexibility. Conclusion: Patients with COVID-19 can suffer from debilitating vision symptoms, including symptoms such as visual fatigue and headaches, as well as signs, including constricted kinetic fields, accommodation, and binocular eye movement problems. This case illustrates that photobiomodulation combined with NORT can lead to significant symptom reduction and improvement in accommodation in COVID-19 patients.